PENGELOLAAN KEUANGAN DAERAH TERHADAP KEMANDIRIAN DAERAH KOTA PRABUMULIH: PENGELOLAAN KEUANGAN DAERAH TERHADAP KEMANDIRIAN DAERAH KOTA PRABUMULIH - febrina, poppy; Alfin Lubay Putra (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2023)
The low ability of the regions to explore local original sources is reflected in the relatively small receipt of Regional Original Income (PAD) compared to total regional revenues and the lack of effort and ability of local governments to manage and explore existing sources of income. Therefore, the purpose of this study is to measure the regional fiscal capacity in supporting the economic independence of Prabumulih City, to identify what factors are influential in order to increase PAD in order to support the economic independence of Prabumulih City and how to increase PAD in order to achieve economic independence of Prabumulih City. The analysis of Prabumulih's Financial Performance in this study is an assessment process regarding the level of progress in achieving the work/activities of the Prabumulih City Government in the financial sector for the 2015-2020 period. The ratios used by researchers in analyzing Prabumulih's financial performance in this study are: Degree Ratio of Fiscal Decentralization, Regional Financial Independence Ratio and PAD Effectiveness Ratio.